Hydrological response to future precipitation extremes under climate change. Issue 1 (December 2020) - Li, G H; Chen, Z N; Li, J; Wen, X
Abstract: Adaptive management of future flood disasters is necessary under climate change. In this study, a Generalized Extreme Value (GEV) distribution based statistical model was established to simulate historical and future precipitation extremes in the Xin'an River basin, and the vertical mixed runoff model was driven by future precipitation extremes to simulate the hydrological response to extreme flood events. Compared to precipitation events for the period 1951-2017, the intensity of monthly extreme precipitation for the period 2020-2099 would be increased by 10.4%, 11.0% and 11.4% at a 10-, 20- and 50-year return period, respectively. Future precipitation extremes with a 10-, 20- and 50-year return period were used to drive the calibrated vertical mixed flow model and to simulate the hydrological response of the Xin'an River basin. The runoff peak is increased from 4930 m 3 /s for p=10% to 6525 m 3 /s for p=2%, while the flood volume is increased from 4.26 billion m 3 for p=10% to 5.68 billion m 3 for p=2%, respectively. The hydrological response to precipitation extremes identified herein can serve as a foundation for adaptive flood control operation in the future.